Cement stabilized rammed earth as a sustainable construction material. (15th February 2016) - Kariyawasam, K.K.G.K.D.; Jayasinghe, C.
Highlights: Strength and durability properties of CSRE together with design requirements were established. Sandy laterite soil stabilized with 6% or more cement can be recommended for CSRE. Multipurpose applications of CSRE in buildings, roads and retaining walls are presented. CSRE is a sustainable construction material of desirable strength and durability together with lower life cycle cost. Abstract: In a world where the exploitation of natural resources by the construction industry has become a severe problem, earth can represent an ideal building material that has the potential to reduce the carbon footprint when a cradle to grave life cycle approach is considered. This can also ensure minimum damage to the environment since one day in future, earth obtained can be returned, but could be in a slightly modified form. However, it is very important to consider ways to eliminate the undesirable properties of soil and convert it to a strong and durable building material that would be environmentally friendly. Stabilizing earth with cement and ramming at optimum moisture content forms cement stabilized rammed earth (CSRE), a building material with sufficient strength and durability but low in embodied energy. This paper covers a detailed research carried out on CSRE to establish strength and durability properties together with applications in the form of pilot projects. Sandy laterite soil available in the tropical regions has been identified as a preferable ingredient for CSRE construction which can offer adequate compressive and flexural strengths when cement content is in excess of 6%. Wet strength, erosion resistance and shrinkage properties were assessed and appropriate guidelines are proposed to ensure the durability of CSRE. Further, successful applications of CSRE are highlighted in different forms of construction including housing, roads and retaining walls.